Factors Caused The Convertion of Agricultural And Into A Residential Area In Belayung Baru Village - Monalisa Rahman; Bambang Subiyakto; Rusmaniah Rusmaniah; Jumriani Jumriani; M. Ridha Ilhami (Universitas Lambung Mangkurat, 2024)
Kertak Hanyar District is a sustainable food agriculture area with the potential and functionality intended for rice in wetlands and drylands. This makes Kertak Hanyar sub-district one of the local paddy or rice-producing areas in Banjar Regency. However, currently most of the agricultural land in Kertak Hanyar District, especially in Belayung Baru Village, has been converted into residential areas, so its contribution is relatively small to rice production in Banjar Regency. The aim of writing this article is to describe why agricultural land can be converted into a community residential area in Belayung Baru Village. In this research, the approach used is a descriptive qualitative approach. Data collection techniques were carried out by observing, interviewing, documenting, recording, and studying literature. The results of this research describe that the factors causing the conversion of agricultural land into residential areas in Belayung Baru Village are strategic location, relatively high land prices, and population growth occurring in the capital city of Banjarmasin, which has an impact on the conversion of agricultural land into residential areas in Belayung Baru Village, Kertak Hanyar District as well as ease of licensing housing construction by the Regional Government.